Resolving the spatial architecture of myeloma and its microenvironment at the single-cell level - John, Lukas; Poos, Alexandra; Brobeil, Alexander; Schinke, Carolina; Huhn, Stefanie; Prokoph, Nina; Lutz, Raphael; Wagner, Barbara; Zangari, Maurizio; Tirier, Stephan Marius; Mallm, Jan-Philipp; Schumacher, Sabrina; et al. (Nature Communications, 2023)
Abstract - In multiple myeloma spatial differences in the subclonal architecture, molecular signatures and composition of the microenvironment remain poorly characterized. To address this shortcoming, we perform multi-region sequencing on paired random bone marrow and focal lesion samples from 17 newly diagnosed patients. Using single-cell RNA- and ATAC-seq we find a median of 6 tumor subclones per patient and unique subclones in focal lesions. Genetically identical subclones display different levels of spatial transcriptional plasticity, including nearly identical profiles and pronounced heterogeneity at different sites, which can include differential expression of immunotherapy targets, such as CD20 and CD38. Macrophages are significantly depleted in the microenvironment of focal lesions. We observe proportional changes in the T-cell repertoire but no site-specific expansion of T-cell clones in intramedullary lesions. In conclusion, our results demonstrate the relevance of considering spatial heterogeneity in multiple myeloma with potential implications for models of cell-cell interactions and disease progression.
Gesehen am 09.01.2024